Tracing social interactions in Pleistocene North America via 3D model analysis of stone tool asymmetry - Sholts, Sabrina B.; Gingerich, Joseph A. M.; Schlager, Stefan; Stanford, Dennis J.; Wärmländer, Sebastian K. T. S. (2017)
Abstract: Stone tools, often the sole remnant of prehistoric hunter-gatherer behavior, are frequently used as evidence of ancient human mobility, resource use, and environmental adaptation. In North America, studies of morphological variation in projectile points have provided important insights into migration and interactions of human groups as early as 12–13 kya. Using new approaches to 3D imaging and morphometric analysis, we here quantify bifacial asymmetry among early North American projectile point styles to better understand changes in knapping technique and cultural transmission. Using a sample of 100 fluted bifaces of Clovis and post-Clovis styles in the eastern United States ca. 13,100–9,000 cal BP (i.e., Clovis, Debert-Vail, Bull Brook, Michaud-Neponset/Barnes, and Crowfield), we employed two different approaches for statistical shape analysis: our previously presented method for analysis of 2D flake scar contours, and a new approach for 3D surface analysis using spherical harmonics (SPHARM). Whereas bifacial asymmetry in point shape does not vary significantly across this stylistic sequence, our measure of asymmetric flake scar patterning shows temporal variation that may signify the beginning of regionalization among early New World colonists